Ambulatory blood pressure monitoring for cardiovascular medicine. - Kario, K. (IEEE Engineering in medicine and biology magazine)
Discusses evaluating blood pressure (BP) behavior outside of the clinical setting and during daily activities to identify high-risk subjects. It is concluded that various valuable information on the cardiovascular system can be obtained using multifunctional ambulatory BP monitors. Wearable monitoring of BP and other cardiovascular variables would be useful for chronobiological strategy for risk stratification and more effective individualized prevention and treatment of cardiovascular events.